Faktor Terkait Kesenjangan Ekonomi dan Kesejahteraan - Prawesti Ningrum, Endah; M, Sumarno; Endah Nursyamsi, Sari; Siregar, Nasaruddin (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2024)
Economic disparity is a complex phenomenon that has a significant impact on sustainable income growth. Several related factors can be identified as the main causes of this gap. First, unequal population conditions contribute to unequal income distribution. In addition, inequalities in access to education and economic resources exacerbate the situation, preventing certain individuals and communities from having equal opportunities to develop. Uneven infrastructure development also plays a role in widening the gap, with underserved areas tending to experience economic stagnation. Lack of employment opportunities, especially in areas with high unemployment rates, further deepens the problem. The literature review shows that inductive qualitative analysis can provide a deeper understanding of the dynamics of this economic gap. From the results, it can be concluded that to address the economic gap, there needs to be an integrated effort that includes equalizing access to education, resources, and improving infrastructure in less developed areas. This strategy will not only promote inclusive economic growth, but also improve the overall welfare of society. Therefore, policies that focus on empowerment and job creation should be prioritized in efforts to reduce economic disparities at various levels. With a comprehensive approach, a more just and sustainable society for all is expected.